Selenium and the thyroid: A close-knit connection - Bhuyan, Ashok K. (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: In areas with severe selenium deficiency higher incidence of thyroiditis has been reported due to a decreased activity of selenium-dependent glutathione peroxidase enzyme within thyroid cells. AIMS AND OBJECTIVE: To study the effect of selenium supplementation in patients with autoimmune thyroid disease. MATERIALS AND METHODS: This is a blinded placebo-controlled prospective study done in 60 patients with autoimmune thyroid disease (as defined by an anti-thyroid peroxidase antibody (TPOAb) level more than 150 IU/ml) irrespective of the baseline thyroid status. Patients with overt hyperthyroidism who are on antithyroid drugs, patients on any other medication, which may alter the immunity status of the patients, and pregnant patients were excluded from the study. Patients were randomized into two age and TPOAb-matched groups; 30 patients received 200 μg of sodium selenite/day, orally, for 3 months, and 30 patients received placebo. All hypothyroid patients were given l-thyroxine replacement. RESULTS: Of 30 patients in the selenium treated group, 6 patients were overtly hypothyroid, 15 were subclinical hypothyroid, 6 were euthyroid, and 3 were subclinical hyperthyroid. The mean TPOAb concentration decreased significantly by 49.5% (P < 0.013) in the selenium treated group versus 10.1% (P < 0.95) in the placebo-treated group. CONCLUSION: Selenium substitution has a significant impact on inflammatory activity in thyroid-specific autoimmune disease. It would be of interest to determine whether early treatment with selenium in patients with newly developed autoimmune thyroiditis may delay or even prevent the natural course of these diseases.